Atypical hemolytic uremic syndrome with a C3 variant following COVID-19: a case report - Ando, Masato; Kubota, Kazuo; Kadowaki, Saori; Kawamoto, Minako; Kawamoto, Norio; Okamoto, Haruka; Nagaya, Soichiro; Miwa, Yuki; Ohnishi, Hidenori (Frontiers in Pediatrics, 2025)
Atypical hemolytic uremic syndrome (aHUS) is a form of thrombotic microangiopathy (TMA) characterized by the triad of microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury, and is caused by overactivation of the alternative complement pathway. A 13-year-old Japanese boy with an unremarkable medical history developed symptoms of TMA following coronavirus disease 2019 (COVID-19) infection with mild respiratory symptoms. He was eventually diagnosed with aHUS with a gain-of-function C3 variant. He improved with supportive therapy and plasma exchange, and did not require anti-C5 antibody therapy. In the literature, more than 20 cases of de novo or relapsed aHUS have been described following COVID-19. It has been shown that the complement lectin pathway can be activated by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike and N proteins, and the alternative pathway can be activated by the SARS-CoV-2 spike protein. The current case highlights the possibility that COVID-19, even when respiratory symptoms are not severe, can trigger aHUS.